EFEKTIVITAS EKSTRAK DAUN KATUK (Sauropus androgynus (L) Merr) SEBAGAI VERMISIDAL TERHADAP KEMATIAN CACING Fasciola sp SECARA in vitro - Dwipal Tio Ikhsan Hadi; Mashur; Kholik; Katty Hendriana Priscilia Riwu (JURNAL SANGKAREANG MATARAM, 2024)
Fasciolosis is a parasitic disease that attacks ruminants and often causes losses among farmers in the form of decreased livestock productivity levels and even causes death in livestock. this study aims to determine the vermicidal effect of katuk (Sauropus androgynus (L.) Merr) leaf extract against fasciola sp. in vitro in terms of the length of time of death. the samples used in this study were fasciola worms taken from the Majeluk Slaughterhouse (RPH). this study used a completely randomized design (CRD) with 7 treatments with 3 repetitions, the treatments in this study consisted of katuk (Sauropus androgynus (L.) Merr) leaf extract concentrations of 2.5%, 3.5% and 4.5%. Albendazole with concentrations of 2.5%, 3.5% and 4.5% and negative control using distilled water. the data obtained were analyzed by analysis of variance (ANOVA), further tested using the Duncan test. the results of this study showed that the treatment of katuk (Sauropus androgynus (L.) Merr) leaf extract with concentrations of 2.5%, 3.5%, 4.5% had a significantly different effect (P>0.05) in accelerating the death time of fasciola sp compared to the negative control (distilled water), but was still lower than the Albendazole treatment. Albendazole, even at the lowest concentration (2.5%), caused the death of worms faster than cotton leaf extract.